The impact of early life stress and schizophrenia on motor and cognitive functioning: an experimental study - Oginga, Fredrick Otieno; Mpofana, Thabisile (Frontiers in Integrative Neuroscience, 2023)
Background: Early life stress (ELS) and parental psychopathology, such as schizophrenia (SZ), have been associated with altered neurobiological and behavioral outcomes later in life. Previous studies have investigated the effects of ELS and parental SZ on various aspects of behavior, however by combining these stressors aimed to explore their interactive effects, as individuals in real-life situations may experience multiple stressors simultaneously.The aim of this study was to investigate the impact of ELS and schizophrenia on locomotor activity, anxiety-like behavior, exploratory tendencies and spatial memory in Sprague Dawley (SD) rats.: Male and female SD pups were randomly assigned to eight groups: control, ELS, schizophrenia, and ELS + schizophrenia. ELS was induced by prenatal stress (maternal stress) and maternal separation (MS) during the first two weeks of life, while SZ was induced by subcutaneous administration of ketamine. Behavioral tests included an open field test (OFT) for motor abilities and Morris water maze (MWM) for cognitive abilities. ANOVA and post hoc Tukey tests were utilized to analyze the data.Results: Our results show that ELS and parental psychopathology had enduring effects on SZ symptoms, particularly psychomotor retardation (p < 0.05). The OFT, revealed increased anxietylike behavior in the ELS group (p = 0.023) and the parental psychopathology group (p = 0.017) 2 compared to controls. The combined ELS and parental psychopathology group exhibited the highest anxiety-like behavior (p = 0.006). The MWM analysis indicated impaired spatial memory in the ELS group (p = 0.012) and the combined ELS and parental psychopathology group (p = 0.003) compared to controls. Significantly, the exposure to ELS resulted in a decrease in the population of glial fibrillary acidic protein-positive (GFAP+) astrocytes. However, this effect was reversed by positive parental mental health.Our findings highlight the interactive effects of ELS and parental psychopathology on anxiety-like behavior and spatial memory in rats. ELS was linked to increased anxiety-like behavior, while SZ was associated with anhedonia-like behavior. Positive parenting augment neuroplasticity, synaptic function, and overall cognitive capacities.